Engineering innate immunology in cardiovascular disease models and regenerative medicine - O'Rourke, Sinead (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2023)
Heart failure is the leading cause of death worldwide with atherosclerosis and myocardial infarction remaining prominent causes. It is now widely accepted that the inflammatory response holds a key role in advancing both cardiovascular disease and heart failure, and as a result, anti-inflammatory therapies have garnered significant interest in the last decade to combat disease. In particular, targeting the inflammatory action of macrophages, an innate immune cell population known for their adverse pathological role in both cardiovascular disease and heart failure, shows great promise. However, advances in immunomodulatory therapies, including those which target macrophages, remain limited in humans. This is in part due to substantial gaps in our knowledge regarding the interactions of the immune response in the heart at a cellular level and further complicated by the fact that current disease models either fail to incorporate a multicellular environment, or are carried out in animal models, which can largely lack translational capacity. The aim of this thesis, therefore, was to assess the role of macrophages in the cardiac environment at a simpler cellular level, with the intention of elucidating the functional role of macrophages in the heart, gaining insight to the mechanisms which advance CVD, and ultimately identifying potential therapeutic strategies for future treatments of heart failure. To achieve this, I explored several different factors which can influence macrophage function in the cardiac environment, including cell-cell interactions with cardiomyocytes, endogenous athero-associated DAMPs, and the physical stimulus: electrical stimulation. First, I assessed the interactions between primary human macrophages and induced pluripotent stem cell-derived cardiomyocytes, in order to understand how cardiomyocyte cross-talk influences macrophage function. It was observed in this study that cardiomyocytes potentially have an immunomodulatory effect on blood-derived macrophages, limiting the production of pro-inflammatory cytokine IL-6 and chemokine IL-8. However, detailed characterisation of this response was limited by the adverse effects of B-27? supplement, a media component necessary for the culture of induced pluripotent stem cell-derived cardiomyocytes. The second study of this thesis investigated the impact of cholesterol crystals on primary human macrophages. It was demonstrated in this chapter that cholesterol crystals promote polarisation of macrophages towards a pro-inflammatory M1 phenotype, with increased expression of M1 associated genes and IL-8 production. This pro-inflammatory response was accompanied by increased rates of glycolysis in macrophages. Inhibition of glycolysis either directly through inhibition of the glycolytic enzymes Hexokinase II (HK2), or PFKFB3, or else indirectly through inhibition of PKM2 (found to be a critical mediator of macrophage metabolic reprogramming) abrogated the pro-inflammatory phenotype induced by cholesterol crystals. As a result of this study, significant insight was gained regarding the inner mechanisms which drive macrophage-mediated inflammation in atherosclerosis, while furthermore highlighting immunometabolism as a novel therapeutic target to combat this disease. The third study of this thesis investigated the impact of electrical stimulation on macrophage phenotype and function. It was observed in this work that electrical stimulation promotes polarisation of primary human macrophages towards an anti-inflammatory M2 phenotype, with increased expression of M2 associated genes and pro-regenerative growth factors. Additionally, electrical stimulation restricted classical activation of macrophages with either LPS or cholesterol crystals. This work has allowed us to shed some light on how homeostasis of macrophages is potentially maintained in the heart while additionally, presenting a novel therapeutic strategy to harness anti-inflammatory, pro-regenerative responses across multiple injury and defence microenvironments. Based on the above findings, the fourth and final study of this thesis assessed the response of macrophages to the electroconductive material PEDOT: PSS, for future applications of electrically stimulated macrophages. PEDOT: PSS was found to be well tolerated by primary human macrophages, not only identifying the material as a compatible platform for macrophage culture in vitro, but also providing insight to future success of the material in vivo as PEDOT: PSS failed to elicit a foreign body response in macrophages. Collectively, the work in this thesis has provided novel insight to the function of human macrophages in the cardiac environment, providing insight to the chemical and physical factors which shape the supportive role of macrophages, while additionally demonstrating the cellular mechanisms responsible for adverse function of this cell population in cardiovascular disease.
APPROVED
Keywords: Immunology; Biomedical Engineering; Tissue engineering; Cardiovascular Disease; Disease models